Analysis of differential metabolites in Liuyang douchi at different fermentation stages based on untargeted metabolomics approach - Liwen Jiang; Yi Chen; Tiantian Zhao; Pao Li; Luyan Liao; Yang Liu (Food Chemistry: X)
The quality and flavor of Liuyang Douchi are usually closely related to the metabolites compostion. This work described the metabolic profiles of Liuyang douchi during fermentation. Obvious hydrolysis of carbohydrates, proteins and slight lipids degradation were observed. Notably, the qu-making and pile-fermentation stage of douchi could be easily distinguished according to their metabolites profile, and pile-fermentation stage showed the most abundant metabolites. Specifically, organic acid, such as succinic acid and lactic acid, accumulated during pile-fermentation, as well as amino acids and derivatives. Especially glutamate (Glu), which contributed to the umami taste, increased form 0.82 mg/g to 15.90 mg/g after fermentation. Meanwhile, metabolisms related to amino acids were also the main enrichment metabolic pathways. Among them, some flavor compunds such as phenylacetaldehyde might drived from phenylalanine metabolism. These results could provide a new understanding on the metabolic characteristics during Liuyang douchi fermentation.